2021
DOI: 10.1088/1757-899x/1119/1/012019
|View full text |Cite
|
Sign up to set email alerts
|

Image segmentation with Kapur, Otsu and minimum cross entropy based multilevel thresholding aided with cuckoo search algorithm

Abstract: Color image segmentation is the primary factor to provide the intended information from the input image. The straightforward method called multilevel thresholding (MLT) is used to analyse the various classes of complex images. But, when the level of threshold increases, computational difficulty increases. Hence, MLT with most promising objective functions such as Kapur, Otsu and minimum cross entropy aided with cuckoo search algorithm (CSA) is used. The efficient metaheuristic cuckoo search algorithm’s control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…The optimization process hinges on the mean values within each region of the given image. Numerous entropy-based thresholding models have emerged to address data separation challenges [16][17][18]. The application of cross-entropy approaches has paved the way for advancements in image segmentation within the literature.…”
Section: Minimum Cross-entropy Thresholding (Mcet)mentioning
confidence: 99%
“…The optimization process hinges on the mean values within each region of the given image. Numerous entropy-based thresholding models have emerged to address data separation challenges [16][17][18]. The application of cross-entropy approaches has paved the way for advancements in image segmentation within the literature.…”
Section: Minimum Cross-entropy Thresholding (Mcet)mentioning
confidence: 99%
“…For example, determining white matter (WM) and grey matter volume in brain magnetic resonance images (MRI) has become an important measurement tool for multiple sclerosis (MS) patient monitoring and research [3][4][5]. A number of different approaches for brain tissue segmentation have been identified in the literature, including histogram-based techniques, edge detection, regionbased segmentation [6,7], fuzzy clustering [8][9][10][11][12], graph cuts [13,14], genetic algorithms [15][16][17], threshold approaches [18][19][20][21], and hybrid techniques [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…Numerical results clearly demonstrated that proposed ICS with Otsu objective function provided promising outcomes. Kalyani et. al.…”
Section: Introductionmentioning
confidence: 99%